KEPEMIMPINAN TRANSAKSIONAL DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN MELALUI MOTIVASI KERJA KARYAWAN - Khilmi Izdiana; Naili Farida; Andi Wijayanto (Jurnal Ilmu Administrasi Bisnis, 2014)
Human resource is one resource that has a very important role in a variety of sectors , because human resources is a factor to mobilize other resources . Human resources need special attention in handling from its management to improve employee performance. This study aims to determine whether there is influence between Transactional Leadership (X1), Cultural Organization (X2) on employee performance (Y2) Through the Work Motivation (Y1). The population of this study were 70 employees as respondent. Likert scale was used as measurement scale. Linear regression and path analysis were used in the data analysis with SPSS 20.00. The results of partially  data processing shows that each Transactional Leadership, Organizational Culture, and Work Motivation influence the performance of employees in PT. Pura Nusapersada unit PM 8 Kudus. The result of path analysis that work motivation as a mediator "boosters" to employee performance due to the indirect effect of 0.383 on the variable of organizational culture. Based on these results, the management of PT. Pura Nusapersada need to consider the application of Transactional Leadership and Organizational Culture as a form of work motivation to improve employee performance. In terms of leadership, a leader must give attention to employees to improve employee performance.